Perubahan Sikap Luar Negeri Filipina terhadap Tiongkok di Laut Cina Selatan Pada Masa Rodrigo Deturde - Mitta Diahalwani; Peni Hanggarini (Journal of Innovative and Creativity, 2025)
This research explores the significant shift in the Philippines' foreign policy towards China in the South China Sea under President Rodrigo Duterte's administration. The South China Sea, rich in natural resources and crucial to global maritime trade, has long been a hotspot for geopolitical tension, particularly due to overlapping territorial claims between China and Southeast Asian nations, including the Philippines. Prior to Duterte, the Philippines adopted a firm and confrontational approach—leveraging international arbitration and military alliances, especially with the United States. However, Duterte pivoted towards a more pragmatic and cooperative stance, opting for bilateral dialogue and economic partnerships with China, including joint ventures in resource exploration and integration within the Belt and Road Initiative. While this strategy aimed to de-escalate regional tensions and stimulate national development, it sparked domestic controversy over issues of national sovereignty and maritime rights. This study analyzes the motivations behind Duterte's diplomatic shift, its implications on Philippine sovereignty, regional dynamics, and the broader balance of power in Southeast Asia. By using qualitative methods and historical-political analysis, the paper concludes that Duterte’s foreign policy realignment marks a strategic recalibration that prioritizes economic gains over territorial assertion, with profound consequences for future Philippine diplomacy.